The Coast-RiskBySea model for climate proof decision-making support - Maria Fabrizia Clemente (Techne)
Climate scenarios require the implementation of climate proof actions. The effectiveness of such projects directly depends on the knowledge of local contexts and on the built environment’s characteristics in relation to climate risk conditions. Innovative methods of knowledge can be implemented through the use of enabling technologies. Based on these considerations, the paper proposes the Coast-RiskBySea model as support for climate proof decision-making in relation to coastal flood risk, with the aim of developing new synergies between environmental design and enabling technologies. The proposed model was tested on an application case in the city of Naples by simulating a climate proof measure to assess the effectiveness of this solution in terms of damage reduction, and to define the potential and criticality of the approach.